Byzantine Octagon Domed Churches of the 11th Century and the Roman Imperial Architecture - Freze, Anna A. (Actual Problems of Theory and History of Art, 2015)
Summing up both the archaeological and textual evidence, it is possible to suggest that octagon domed churches did not appear out of nowhere. After the Iconoclasm era the centralized architectural designs were still the important loci for staging certain distinguished events of the imperial cult of both the living and the deceased emperors. So investigation of the Roman imperial mausolea and palatial aulae used for official ceremonies as the predecessors of the Byzantine architectural designs may yield some significant results. Renewed functioning of the complex of the Holy Apostles and the aulae of the Great Palace confirm that the centralized design and especially the octagonal one, were not only actual for the Byzantine architecture in the 9th–11th centuries, but this pattern was still able to convey a very special content, that of the idea of basilea as the sacral power and status of a Byzantine emperor. Being a viable architectural pattern, the octagonal type may have been seen as a fruitful area for construction and design experiments, and the necessary impulse for them may have been provided by the building activity under Basil I, when his architects had to restore a significant number of the Early Byzantine edifices in Constantinople and its suburbs. Thus, it may be suggested that the extant octagon domed churches of the 11th century, seen from this angle, may be considered as the result of blending the two types of design: cross-in-square church, being a symbol of monastic communities who were gathering strength, and octagonal church still closely linked to imperial/metropolitan commission.
Keywords: Byzantine architecture; Roman Imperial architecture; palatial architecture; octagon; mausoleum